Urethra Sparing With Target Motion Mitigation in Dose-Escalated Extreme Hypofractionated Prostate Cancer Radiotherapy: 7-Year Results From a Phase II Study - Greco, Carlo; Pares, Oriol; Pimentel, Nuno; Louro, Vasco; Nunes, Beatriz; Kociolek, Justyna; Stroom, Joep; Vieira, Sandra; Mateus, Dalila; Cardoso, Maria Joao; Soares, Ana; Marques, Joao; et al. (Frontiers in Oncology, 2022)
Purpose To explore whether the rectal distension-mediated technique, harnessing human physiology to achieve intrafractional prostate motion mitigation, enables urethra sparing by inverse dose painting, thus promoting dose escalation with extreme hypofractionated stereotactic ablative radiotherapy (SABR) in prostate cancer. Materials and Methods Between June 2013 and December 2018, 444 patients received 5 × 9 Gy SABR over 5 consecutive days. Rectal distension-mediated SABR was employed via insertion of a 150-cm3 air-inflated endorectal balloon. A Foley catheter loaded with 3 beacon transponders was used for urethra visualization and online tracking. MRI-based planning using Volumetric Modulated Arc Therapy - Image Guided Radiotherapy (VMAT-IGRT) with inverse dose painting was employed in delivering the planning target volume (PTV) dose and in sculpting exposure of organs at risk (OARs). A 2-mm margin was used for PTV expansion, reduced to 0 mm at the interface with critical OARs. All plans fulfilled Dmean ≥45 Gy. Target motion ≥2 mm/5 s motions mandated treatment interruption and target realignment prior to completion of the planned dose delivery. Results Patient compliance to the rectal distension-mediated immobilization protocol was excellent, achieving reproducible daily prostate localization at a patient-specific retropubic niche. Online tracking recorded ≤1-mm intrafractional target deviations in 95% of treatment sessions, while target realignment in ≥2-mm deviations enabled treatment completion as scheduled in all cases. The cumulative incidence rates of late grade ≥2 genitourinary (GU) and gastrointestinal (GI) toxicities were 5.3% and 1.1%, respectively. The favorable toxicity profile was corroborated by patient-reported quality of life (QOL) outcomes. Median prostate-specific antigen (PSA) nadir by 5 years was 0.19 ng/ml. The cumulative incidence rate of biochemical failure using the Phoenix definition was 2%, 16.6%, and 27.2% for the combined low/favorable–intermediate, unfavorable intermediate, and high-risk categories, respectively. Patients with a PSA failure underwent a 68Ga-labeled prostate-specific membrane antigen (68Ga-PSMA) scan showing a 20.2% cumulative incidence of intraprostatic relapses in biopsy International Society of Urological Pathology (ISUP) grade ≥3. Conclusion The rectal distension-mediated technique is feasible and well tolerated. Dose escalation to 45 Gy with urethra-sparing results in excellent toxicity profiles and PSA relapse rates similar to those reported by other dose-escalated regimens. The existence of intraprostatic recurrences in patients with high-risk features confirms the notion of a high α/β ratio in these phenotypes resulting in diminished effectiveness with hypofractionated dose escalation.